Automated question extraction and tagging for cloud-based online communities. (15th August 2019) - Jangiti, Saikishor; Swathi, G.; Ravi, Logesh; Vijayakumar, V.; Subramaniyaswamy, V.
Crowd-based question answering forums and cloud-based community question answering platforms provide us with the dais to post questions and answers online. This helps the users to get desired answers from expert users. It is a challenge for a person with mobility needs to go out and explore. The 'wheelchair accessible' information provided by Google Maps is useful to explore before going out. Local guides share this knowledge on Google Maps by answering quick questionnaire. Automated question generation is a key challenge that we face with regard to natural languages in the context of users visited locations, already reviewed places, likes, interests and user experience. In this paper, we have implemented an automatic question generation system that comprises of part-of-speech (POS) tagger, text-to-question generation task using syntactic analysis and a named entity extraction. The proposed system is tested with human effort and is generating valid questionnaire.